2016
DOI: 10.1007/s10452-016-9569-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of species sorting driving aquatic beetles associated with woody debris in a transitional region between Cerrado and Atlantic Forest biomes

Abstract: We investigated (1) the variation of both species composition and species relative abundances of aquatic beetles associated with submerged woody debris in a transitional region between Cerrado (Brazilian savannah) and Atlantic Forest biomes; and (2) which assembling processes are more associated with the observed patterns, species sorting or mass effects. We hypothesized that the marked differences between Cerrado and Atlantic Forest streams regarding vegetation composition and structure would produce differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…This is in line with many studies that advocate that the dichotomisation between environmental selection and stochasticity is an inaccurate portrayal processes structuring real metacommunities (Gravel et al, 2006;Winegardner, Jones, Ng, Siqueira, & Cottenie, 2012). Environmental selection is an important process structuring aquatic insect metacommunities Siqueira, Bini, Roque, Couceiro, et al, 2012), including those in Atlantic Forest streams (Roque et al, 2010;Valente-Neto, Saito, Siqueira, & Fonseca-Gessner, 2016). In this process, species are filtered from patches in which environmental conditions are outside their niche breadth (Leibold et al, 2004;Vellend, 2010) (modelled in both the niche and nichestochastic scenarios).…”
Section: Discussionsupporting
confidence: 79%
“…This is in line with many studies that advocate that the dichotomisation between environmental selection and stochasticity is an inaccurate portrayal processes structuring real metacommunities (Gravel et al, 2006;Winegardner, Jones, Ng, Siqueira, & Cottenie, 2012). Environmental selection is an important process structuring aquatic insect metacommunities Siqueira, Bini, Roque, Couceiro, et al, 2012), including those in Atlantic Forest streams (Roque et al, 2010;Valente-Neto, Saito, Siqueira, & Fonseca-Gessner, 2016). In this process, species are filtered from patches in which environmental conditions are outside their niche breadth (Leibold et al, 2004;Vellend, 2010) (modelled in both the niche and nichestochastic scenarios).…”
Section: Discussionsupporting
confidence: 79%
“…Aquatic Coleoptera is one of the most diverse orders of aquatic macroinvertebrates, exhibiting a wide morphological, functional, and ecological range; they are relatively easy to sample, and their taxonomy and biogeography are reasonably well-known [ 18 ]. Many studies have demonstrated that water beetles respond to variation across space and feature complex diversity patterns in freshwater ecosystems [ 1 , [19] , [20] , [21] , [22] , [23] , [24] , [25] ], but relationships within the four diversity attributes and their variation across wide spatial gradients have not been deeply studied.…”
Section: Introductionmentioning
confidence: 99%